Factors influencing somatic embryogenesis, regeneration, and Agrobacterium-mediated transformation of cassava (Manihot esculenta Crantz) cultivar TME14 - Nyaboga, E.N.; Njiru, J.M.; Tripathi, L. (Frontiers Media, 2015)
Routineproductionoflargenumbersoftransgenicplantsisrequiredtofullyexploitadvancesincassavabiotechnologyandsupportdevelopmentofiprovedgermplasmfordeploymenttofarmers.Thisarticledescribesanimproved,high-efficiencytransformationprotocolforrecalcitrantcassavacultivarTME14preferredinAfrica.Factorsthatfavorproductionoffriableembryogeniccalli(FEC)werefoundtobeuseofDKWmedium,crushingoforganizedembryogenicstructures(OES)through1–2mmsizedmetalwiremesh,washingofcrushedOEStissuesandshortexposureoftyrosinetosomaticembryos;andtransformationefficiencywasenhancedbyuseoflowAgrobacteriumdensityduringco-cultivation,co-centrifugationofFECwithAgrobacterium,germinationofparamomycinresistantsomaticembryosonmediumcontainingBAPwithgradualincreaseinconcentrationandvariationsofthefrequenyofsubcultureofcotyledonary-stageembryosonshootelongationmedium.Byapplyingtheoptimizedparameters,FECwereproducedforcassavacultivarTME14andtransformedusingAgrobacteriumstrainLBA4404harboringthebinaryvectorpCAMBIA2301.About70–80independenttransgeniclinespermlsettledcellvolume(SCV)ofFECwereregeneratedonselectivemedium.HistochemicalGUSassaysconfirmedtheexpressionofgusAgeneintransformedcalli,somaticembryosandtransgenicplants.ThepresenceandintegrationofthegusAgenewereconfirmedbyPCRandSouthernblotanalysis,respectively.RT-PCRanalysisoftransgenicplantsconfirmedtheexpressionofgusAgene.Thisprotocoldemonstratessignificantlyenhancedtransformationefficiencyoverexistingcassavatransformationprotocolsandcouldbecomeapwerfultoolforfunctionalgenomicsandtransferringnewtraitsintocassava.